In vitro evaluation of halogen light-activated vs chemically activated in-office bleaching systems. (September 2013) - Liang, Shanshan; Sa, Yue; Jiang, Tao; Ma, Xiao; Xing, Wenzhong; Wang, Zhejun; Wang, Yining
Abstract: Objectives. To compare the tooth whitening efficacy, temperature and HP concentration changes induced by halogen light-activated and chemically activated in-office bleaching systems. Materials and methods. Twenty-four extracted premolars were randomly divided into two groups ( n = 12): Group BL (35% HP with halogen light activation) and Group OP (38% HP with chemical activation). Tooth color was measured by a spectrophotometer according to the CIE L*a*b* color space system. Temperatures of bleaching gels and pulp chambers during the bleaching process were monitored and recorded by a digital multimeter with K-type thermocouple. HP concentrations were tested before and after treatments by iodometry. ANOVA and paired t -test were used for statistical analyses at the significance of p < 0.05. Results. Tooth whitening resulted in the increase of ΔL* and ΔE and reduction of Δb*. Paired t -tests revealed groups BL had greater ΔE than group OP, however, there was no statistically significant difference in ΔE between them after 3 weeks post-treatment. Maximal temperature rise (ΔT) was found only in group BL, showing the increment of 2.55 and 2.02°C for bleaching gels and pulp chambers, respectively. HP concentrations were higher than baseline values for group OP ( p < 0.001) rather than group BL. Conclusions. Halogen light and chemically activated in-office bleaching systems were both effective for tooth whitening, but halogen light activation could improve the immediate whitening effect. In contrast, chemical activation was a more conservative method due to the little temperature rise in pulp chambers.